Energetics of the all-trans -→ 13-cis isomerization of the retinal chromophore of bacteriorhodopsin: Electronic structure calculations for a simple model system - Woywod, C.; Vallet, V.; Li, J.; Görling, Andreas (5th International Conference on Radiation Damage in Biomolecular Systems, RADAM 2008, 2008)
Understanding the molecular mechanism for the photoinduced transmembrane proton pump in the bacteriorhodopsin system is of fundamental importance. This study attempts to investigate the energetics of the initial step of the proton transport cycle, the photoisomerization of the retinal chromophore. The exact reaction pathway and the question of how many excited electronic states are involved in the internal conversion process are still unresolved. The problem is approached by constructing a reaction coordinate suggested by crystallographic studies for a simplified chromophore model system. The CASSCF and CASPT2 electronic structure methods are employed to calculate the energies of the four lowest lying singlet states as a function of the reaction coordinate. The effect of negatively charged protein residues on the reaction is simulated by inclusion of a negative point charge in the model. The results indicate that trans → cis isomerization around the C =C bond may be accompanied by twisting around the C -C bond in order to drive the proton pump. The presence of a counterion does not seem to reduce the barrier for isomerization or the S-S energy difference but clearly stabilizes the cis-product. At first sight the results appear to support the idea of a participation of no other electronic states beyond S and first singly ππ* excited state in the photoreaction. However, the relevance of this prediction is rather limited because of the small size of the model system. Other states of retinal, corresponding in particular to the partly doubly ππ* excited S state of the model, are likely to have a vertical excitation energy similar to the first singly ππ* excited state or even below. © 2008 American Institute of Physics.